Human Development Report 2007/2008 : fighting climate change : human solidarity in a divided world (United Nations Development Programme ; Palgrave Macmillan, 2007)
The report ...calls for a "twin track approach that combines stringent mitigation to limit 21st Century warming to less than 2°C (3.6° F) with strengthened international cooperation on adaptation. On mitigation, the authors call on developed countries to ... cut greenhouse gas emissions by at least 80% of 1990 levels by 2050. It advocates a mix of carbon taxation, more stringent cap-and-trade programmes, energy regulation, and international cooperation on financing for low-carbon technology transfer. Turning to adaptation, the report warns that inequalities in ability to cope with climate change are emerging as an increasingly powerful driver of wider inequalities between and within counties. It calls on rich countries to put climate change adaptation at the centre of international partnerships on poverty reduction.